2014
DOI: 10.1007/s00198-014-2949-1
|View full text |Cite
|
Sign up to set email alerts
|

Calcifediol versus vitamin D3 effects on gait speed and trunk sway in young postmenopausal women: a double-blind randomized controlled trial

Abstract: Calcifediol improved gait speed in early postmenopausal women compared with vitamin D3 and change in 25(OH)D level was moderately correlated with improvement in gait speed. A benefit on trunk sway could not be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Similar results were observed for the 140 μg bolus (13). As far as clinical outcomes, calcidiol showed beneficial effect on muscle performance, lower extremity function and blood pressure (14). There are few data on the long-term skeletal effects of calcidiol and few studies have compared different therapeutic regimens in terms of effect on vitamin D status and bone metabolism.…”
supporting
confidence: 65%
“…Similar results were observed for the 140 μg bolus (13). As far as clinical outcomes, calcidiol showed beneficial effect on muscle performance, lower extremity function and blood pressure (14). There are few data on the long-term skeletal effects of calcidiol and few studies have compared different therapeutic regimens in terms of effect on vitamin D status and bone metabolism.…”
supporting
confidence: 65%
“…Indeed, no data on falls are available during calcidiol supplementation, while a better muscular performance has been demonstrated [16,39]. We acknowledge that not having included fall assessment in the safety analysis is a limitation of our study.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, some randomized controlled trials have demonstrated increased muscle performance in postmenopausal women supplemented with calcidiol at usual doses with respect to cholecalciferol [16,39], although the risk of falling during calcidiol supplementation has not been assessed yet as a primary outcome. These properties make calcidiol a good alternative to cholecalciferol in the treatment of the widespread vitamin D deficiency and related musculoskeletal consequences (osteomalacia, falls, and fractures), and even the supplement of choice when specific conditions hamper the efficacy of parental vitamin D.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were published between 2000 and 2019. Studies were conducted in the USA , Thailand , China , Switzerland , Australia , Brazil , Japan , Netherland , Denmark , Turkey , Norway , UK , Belgium , Finland and Indonesia . None of the studies were of an international multicentre type.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of the included studies ranged from 20 to 30 531 . The duration of follow‐up ranged from 4 weeks to 60 months .…”
Section: Resultsmentioning
confidence: 99%